Analisis etika bisnis islam terhadap praktik pembulatan harga pada jual beli karet - Mutia Sumarni (IAIN Langsa, 2020)
This study describes the practice of rounding prices on buying and selling rubber in Medang Ara village, Karang Baru District. The purpose of this study was to determine the practice of price rounding on the sale and purchase of rubber and to determine the analysis of Islamic business ethics on the practice of rounding prices on buying and selling rubber in the village of Medang Ara, Karang Baru District. The type of research used is field research. Data collection techniques through observation, interviews and documentation, as well as data analysis techniques with a qualitative descriptive approach.Based on the results of the study note that the price rounding done by Medang Ara village rubber agent is rounding down prices. The agent did this rounding because there was no change which made it difficult to pay for the rubber and the agent thought that rounding was a common thing and was known by farmers, so farmers would be sincere if the money was rounded up. In addition, the price rounding done by an agent is contrary to the basic provisions in Islamic business ethics, namely unity, balance, free will, responsibility and truth, and rounding the price is also contrary to the principles in Islamic business ethics such as honesty and transparency in setting prices.